Apparent competition between two species of aphid via the fungal pathogen Erynia neoaphidis and its interaction with the aphid parasitoid Aphidius ervi - Pope, T; Croxson, E; Pell, J; Godfray, C; Muller, C (2002)
1. Motivated by a community study on aphids and their fungal pathogens, three hypotheses were tested experimentally to investigate the influence of the fungal pathogen, Erynia neoaphidis Remaudière and Hennebert, on aphid population and community ecology. 2. Field experiments were performed in 2 years to test whether two susceptible aphid species on different host plants might interact through the shared fungal pathogen. No strong pathogen-mediated indirect interactions (apparent competition) between populations of pea aphid Acyrthosiphon pisum Harris and nettle aphid Microlophium carnosum Buckton were detected. 3. In the first of the field experiments, pea aphids exposed to the fungus showed a weak tendency to produce more winged dispersal morphs than control populations not exposed to the fungus. In a laboratory test, however, no support was found for the hypothesis that the presence of volatiles from fungus-infected cadavers promotes production of winged offspring. 4. The response of the pea aphid parasitoid Aphidius ervi Halliday to colonies containing hosts infected 1 and 3 days previously was assessed. Wasps initiated fewer attacks on 1-day-old infected colonies than on healthy colonies, with the numbers on 3-day-old fungus-infected colonies intermediate.